Survival strategies for small-scale agro-processors - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
A burning sense of optimism at the start of a new business venture can quickly turn to ashes of disappointment when things go wrong. The best policy is to limit the potential for disaster by careful initial planning, to make provision for the...